Invasive Streptococcus iniae Infections Outside North America - Lau, Susanna K. P. (American Society for Microbiology, 2003)
Streptococcus iniae, a fish pathogen causing infections in aquaculture farms worldwide, has only been reported to cause human infections in North America. In this article, we report the first two cases of invasive S. iniae infections in two Chinese patients outside North America. While the first patient presented with bacteremic cellulitis, which is the most common presentation in previous cases, the second patient represents the first recognized case of S. iniae osteomyelitis. Both S. iniae strains isolated from the two patients were either misidentified or unidentified by three commercial systems and were only identified by 16S rRNA gene sequencing. Since no currently available commercial system for bacterial identification includes S. iniae in its database, 16S rRNA gene sequencing is the most practical and reliable method to identify the bacterium at the moment. In contrast to the distinct genetic profile described previously in clinical isolates from Canada, the present two isolates and a clinical isolate from a Canadian patient were found to be genetically unrelated, as demonstrated by pulsed-field gel electrophoresis. Morphologically, colonies of both isolates were also larger, more beta-hemolytic and mucoid, which differ from the usual morphotype described for S. iniae. Owing to their habit of cooking and eating fresh fish, the Asian population is strongly associated with S. iniae infections. As a result of the difficulty in making microbiological diagnosis in patients with cellulitis and the problem of identification in most clinical microbiology laboratories, the prevalence of S. iniae infections, especially in the Asian population, may have been under-estimated.